Isolation and Selection of Plant Growth Promoting Rhizobacteria from Wedelia trilobata (L.) A.S. Hitchcock Rhizosphere - Sutthisa, Waraporn; Khamjandee, Siriprapa (RMUTP Research Journal Sciences and Technology, 2019)
The objective of this research was to isolate plant growth promoting rhizobacteria from Wedelia trilobata (L.) A.S. Hitchcock and test their basic properties of plant growth promoters. Forty-seven bacteria isolates were obtained including 26 isolates of gram positive, 18 isolates of gram negative and 3 isolates of actinobacteria. Plant growth promoting properties were tested such as nitrogen fixation, siderophore production, phosphate solubilization and indole-3-acetic acid production. After that 8 isolates were selected for studying of root colonization and plant growth promoting properties including BWTM1_MSU, BWTM2_MSU, BWTM5_MSU, BWTM6_MSU, BWWM6_MSU, BWWM8_MSU, BWWM9_MSU and BWWM16_MSU. The results show that BWTM5_MSU evident promote plant growth with the most seed germination (63.33%), high level of root and shoot length with 6.11 cm and 3.89 cm, respectively. As a result, the root and shoot weight was as high as 9.56 mg and 11.33 mg, respectively. It also correlated with the highest production of indole-3-acetic acid up to 421.29 ug/ml. Seven days after sowing, can isolated BWTM5_MSU from rhizoplane and rhizosphere with 9.67x106 cfu/ml and 1.64x1010 cfu/ml, respectively.